Feasibility study of off-shore wind farms in Malaysia - Mekhilef, Saad; Safari, A.; Chandrasegaran, D. (2012)
The paper describes the current situation of wind energy across the world and specifically discusses the offshore wind farm technology. Subsequently, wind energy potentiality and techno- economic feasibility of offshore wind farms is investigated in Malaysia. Analysis was conducted using HOMER software to assess the potential of wind energy along the South China Sea coastline. This study indicates the best sites to set up offshore wind farms in Malaysia while costs associated for wind energy generation are calculated. Also, case studies for two types of Vestas wind turbine models (V- 47 and V-80) are conducted. The analysis shows the feed-in tariff policy reduces the energy price and increases wind farms profitability. Investment, operation and maintenance costs have been evaluated for offshore wind energy system.